Effects of COX1-2/5-LOX blockade in Alzheimer transgenic 3xTg-AD mice - Bitto, Alessandra; Giuliani, Daniela; Pallio, Giovanni; Irrera, Natasha; Vandini, Eleonora; Canalini, Fabrizio; Zaffe, Davide; Ottani, Alessandra; Minutoli, Letteria; Rinaldi, Mariagrazia; Guarini, Salvatore; Squadrito, Francesco; et al. (Inflammation research, 2017)
Objective and design Alzheimer’s disease (AD) is associated with amyloid plaques (Aβ) and hyperphosphorylated tau protein tangles in the brain. We investigated the possible neuroprotective role of flavocoxid, a dual inhibitor of cyclooxygenases-1/2 (COX-1/2) and 5-Lipoxygenase (5-LOX), in triple-transgenic (3xTg-AD) mice. Subjects Mice were 3 months at the beginning of the study. Treatment Animals received once daily for 3-month saline solution or flavocoxid (20 mg/kg/ip). Methods Morris water maze was used to assess learning and memory. Histology was performed to evidence Aβ plaques and neuronal loss, while inflammatory proteins were determined by western blot analysis. Results Saline-treated 3xTg-AD mice showed an impairment in spatial learning and memory (assessed at 6 months of age), and increased expression of inflammatory and apoptotic molecules. Treatment of 3xTg-AD mice with flavocoxid reduced: (1) learning and memory loss; (2) the increased eicosanoid production and the phosphorylation level of amyloid precursor protein (APP-pThr668), Aβ 1–42, p-tau (pThr181), pERK, and the activation of the NLRP3 inflammasome; (3) Aβ plaques; and (4) neuronal loss, compared to saline-treated animals. Conclusions Pharmacological blockade of both COX-1/2 and 5-LOX was able to counteract the progression of AD by targeting pathophysiological mechanisms up- and downstream of Aβ and tau.